Unravelling the deformation process of a compacted paper: in-situ tensile loading, 4D X-ray tomography and image-based analysis. (1st May 2022) - Wu, Dan; Engqvist, Jonas; Barbier, Christophe; Karlsson, Christopher; Hall, Stephen
Abstract: Paper of high extensibility has regained attention due to the recent increase in interest of 3D paper forming for packaging. In-plane compaction has been reported as an effective process to improve paper extensibility. Though tension of compacted paper is generally considered as a reversal process of shrinkage, the exact mechanism involved has not been fully studied. This study investigated the mechanical behaviour of a compacted paper by two types of uniaxial tensile tests: continuous tensile testing with digital image correlation (DIC) and stepwise tensile testing in-situ within an X-ray tomograph enabling 4D analysis and digital volume correlation (DVC). The tests were performed on notched samples taken following three orientations, parallel and perpendicular to the main material (machine) direction and at 45° to this. Surface strains were investigated in the DIC tests with a field of view covering the entire sample. The X-ray tomography imaging enabled observation of individual fibres and quantification of the full tensorial strain in the central region of the samples. Both tests confirmed the existence of micro-crepes in fibre networks and the flattening of the micro-crepes in tension. Incremental strains were highest during the transition between the two linear phases in the load–displacement curves in the DIC tests, and gradually decreased towards a relatively homogeneous distribution in the second linear phase. Correlation of the strain patterns in this transition phase with the location of micro-crepes from both DIC and DVC indicates that the flattening of the crepes occurred mainly in the transition phase. In the later stages of loading, the relatively homogeneous strain distribution and straightening of kinks in individual fibres observed in the tomography images indicate contributions to the overall extensibility from deformation of the entire fibre network as well as from individual fibre deformation in the form of straightening.